2013
DOI: 10.5194/npg-20-819-2013
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelectric structures and turbulence in the atmospheric boundary layer

Abstract: Abstract.Complex electrical measurements with the use of sodar data show that electric field pulsation analysis is useful for electrodynamics/turbulence monitoring under different conditions. In particular, the number of aeroelectric structures (AES) generated per hour is a convenient measure of the turbulence intensity. During convectively unstable periods, as many as 5-10 AES form per hour. Under stable conditions, AES occasionally form as well, indicating the appearance of occasional mixing events reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…We showed that pulsations of E Z in the 0.007-0.05 Hz frequency range had a power law spectrum under both fair-weather and fog conditions. The spectral shape under pre-fog conditions was similar to the Kolmogorov spectra of temperature, with the spectral index close to -5/3 in the inertial subrange, and wind velocity variations in a turbulent atmosphere (Anderson 1982;Anisimov et al 2013;Nosov et al 2019). One of possible mechanisms of coupling between electric field and temperature fluctuations is based on the light ion mobility variations induced by a temperature change (Anisimov et al 2001(Anisimov et al , 2013.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations

Polish Polar Research

Shumilov,
Kasatkina,
Makarov
et al. 2021
“…We showed that pulsations of E Z in the 0.007-0.05 Hz frequency range had a power law spectrum under both fair-weather and fog conditions. The spectral shape under pre-fog conditions was similar to the Kolmogorov spectra of temperature, with the spectral index close to -5/3 in the inertial subrange, and wind velocity variations in a turbulent atmosphere (Anderson 1982;Anisimov et al 2013;Nosov et al 2019). One of possible mechanisms of coupling between electric field and temperature fluctuations is based on the light ion mobility variations induced by a temperature change (Anisimov et al 2001(Anisimov et al , 2013.…”
Section: Discussionmentioning
confidence: 56%
“…The spectral shape under pre-fog conditions was similar to the Kolmogorov spectra of temperature, with the spectral index close to -5/3 in the inertial subrange, and wind velocity variations in a turbulent atmosphere (Anderson 1982;Anisimov et al 2013;Nosov et al 2019). One of possible mechanisms of coupling between electric field and temperature fluctuations is based on the light ion mobility variations induced by a temperature change (Anisimov et al 2001(Anisimov et al , 2013. Otherwise, oscillations of the medium velocity during turbulence might lead to the electric-charge mixing, i.e., to small-scale pulsations (Anisimov et al 2001).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations

Polish Polar Research

Shumilov,
Kasatkina,
Makarov
et al. 2021
“…It was shown that the presence of one (in the evening hours of Universal Time) or two (in the evening hours of Universal Time and at local noon) maxima are characteristic of the above variation [16]. The detection of the diurnal variation according to data of the ground-based monitoring of the electric field requires analysis of long-term time series with allowance for the fair-weather conditions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%